2020
DOI: 10.4314/rjmhs.v2i3.14
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to medication administration errors and barriers to self-reporting among nurses: a review of literature

Abstract: Background Medication Administration Errors (MAEs) are common among nurses and can threaten all patients' outcomes. Furthermore, MAEs are the leading cause of incidents in patient safety records worldwide. Objective To review the types of medication administration errors, factors contributing to MAEs and barriers to self-reporting among nurses. Methods A review of the literature was done and included original articles and grey literature from January 2011 until July 2017. An advanced search was done in Medline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…According to this study, the unavailability of the guideline was found to be significantly associated with medication administration error which was supported by research conducted in Egypt. 1 , 37 One of WHO strategy in 2017 was to provide guidelines and strengthen health professional’s capacity through skill-building. The availability of guidelines for medication administration may improve the quality of nursing care and reduce medication administration errors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to this study, the unavailability of the guideline was found to be significantly associated with medication administration error which was supported by research conducted in Egypt. 1 , 37 One of WHO strategy in 2017 was to provide guidelines and strengthen health professional’s capacity through skill-building. The availability of guidelines for medication administration may improve the quality of nursing care and reduce medication administration errors.…”
Section: Discussionmentioning
confidence: 99%
“…MAE is any preventable act that contributes to the failure of proper medication use in the treatment process resulting in harm for the patient to the extent of disability and death. 1,2 It affects human relationships, threatens trust in the healthcare system as a whole, and can also destroy life. [3][4][5] Errors in medication administration can occur through failures in any of the ten rights which are right patient, right medication, right time, right dose, right route, right education/advice, rights to refuse, right assessment, right evaluation/ response, and documentation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When nurses were asked to state the causes of early or late WTMAEs, late WTMAEs were mostly attributed to work overload (88.9%) and this is consistent with the nurses to patient ratio reported in this study which was 1 nurse to greater than 20 patients. Other studies done in France (Berdot et al, 2012), Ethiopia (Feleke et al, 2015) and Rwanda (Nkurunziza et al, 2019) also highlighted work overload as the main cause of administration errors. Tauifiq (2015) reported that medications received late from pharmacy and work overload were the main reason for the cause of late WTMAEs.…”
Section: Discussionmentioning
confidence: 93%